The efficacy of immunotherapy in non-small cell lung cancer with KRAS mutation: a systematic review and meta-analysis - Rui Zhao; Yang Shu; Wei Xu; Fengxian Jiang; Pancen Ran; Liying Pan; Jingliang Wang; Weihao Wang; Jing Zhao; Yahui Wang; Guobin Fu (Cancer Cell International)
Abstract Purpose The KRAS mutation is highly prevalent in NSCLC and is associated with poor efficacy of immunotherapy. Nevertheless, the impact of KRAS mutation, mutation subtypes, and co-mutations on the effectiveness of immunotherapy remains uncertain. This study aimed to assess the influence of the KRAS mutation on the effectiveness of immunotherapy in NSCLC, specifically examining different subtypes of KRAS mutations and co-mutations. Methods We performed an extensive search of multiple databases, covering the period from January 1, 2000, to December 5, 2023. A total of 24 articles met our inclusion criteria and were included in this study. A comparative analysis assessed the influence of different subgroups, including KRAS mutation, KRAS wild-type, KRAS G12C mutation, KRAS G12D mutation, and KRAS with co-mutations in NSCLC with immunotherapy. The study outcomes include HR, with corresponding 95% CI and P-values for OS and PFS using Review Manager 5.4 software for the meta-analysis. Result The KRAS mutation appears to have a more beneficial impact on OS (HR 0.54 [95% CI: 0.41–0.71]; P < 0.00001) and PFS (HR 0.63 [95% CI: 0.53–0.76]; P < 0.00001) in NSCLC patients receiving immunotherapy compared to those without immunotherapy. The presence of KRASG12C mutation has been found to have a positive impact on PFS (HR 0.39 [95% CI: 0.25–0.62]; P < 0.0001) in NSCLC patients who undergo immunotherapy, compared to those who did not receive immunotherapy. KRAS non-G12D mutation is considerably associated with longer OS (HR 1.52 [95% CI: 1.10–2.10]; P = 0.01). The clinical benefit in OS between patients without STK11 co-mutation and those who have KRAS mutation with STK11 is significant (HR 1.46 [95% CI: 1.10–1.93]; P = 0.008). Comparing the impact of OS patients without KEAP1/NFE2L2 mutation to those with KRAS and KEAP1/NFE2L2 co-mutations showed a significant impact (HR 1.89 [95% CI: 1.33–2.68]; P = 0.0004). Conclusion The KRAS mutation and KRAS G12C mutation confer benefits that impact OS and PFS in NSCLC patients treated with immunotherapy. However, the KRAS G12D mutation negatively impacts OS compared to the KRAS non-G12D mutation. Furthermore, KRAS co-mutations involving STK11 and KEAP1/NFE2L2 are associated with a negative impact on the efficacy of immunotherapy in NSCLC patients.